Relationship between neuropsychiatric signs and symptoms and SARS-CoV-2 infection: an integrative review (Research, Society and Development, 2022)
Introduction: Several viruses, including CoVs, can affect the nervous system, causing neuropsychiatric signs and symptoms. Because this is an unknown disease widely spread, there are few studies that deal with the effects of the SARS-CoV-2 on the nervous system. Objective: To describe the relationship between neuropsychiatric signs and symptoms and SARS-Cov-2 virus infection. Methods: integrative review conducted in the Pubmed Portal, Virtual Health Library, Cochrane and the academic researcher Science Direct. The works were analyzed qualitatively, with the narrative description divided into four thematic categories. Results: 1024 studies were found and 48 studies selected to compose this integrative review. There is a pathophysiological relationship of SARS-Cov-2 infection and the involvement of the Central Nervous System and Peripheral Nervous System through different pathways and mechanisms. Conclusion: Monitoring patients during and after COVID-19 can minimize the neuropsychiatric sequelae resulting from this disease, especially in elderly patients with comorbidities.